Transcriptomic and Metabolomic Analysis Revealed Roles of Yck2 in Carbon Metabolism and Morphogenesis of Candida albicans - Liboro, Karl; Yu, Seong-Ryong; Lim, Juhyeon; So, Yee-Seul; Bahn, Yong-Sun; Eoh, Hyungjin; Park, Hyunsook (Frontiers in Cellular and Infection Microbiology, 2021)
Candida albicans is a part of the normal microbiome of human mucosa and is able to thrive in a wide range of host environments. As an opportunistic pathogen, the virulence of C. albicans is tied to its ability to switch between yeast and hyphal morphologies in response to various environmental cues, one of which includes nutrient availability. Thus, metabolic flexibility plays an important role in the virulence of the pathogen. Our previous study has shown that C. albicans Yeast Casein Kinase 2 (CaYck2) regulates the yeast-to-hyphal switch, but its regulatory mechanisms remain unknown. This study further elucidated the role of Yck2 in governing morphology and carbon metabolism by analyzing the transcriptome and metabolome of the C. albicans YCK2 deletion mutant strain (yck2Δ strain) in comparison to the wild type strain. Our study revealed that loss of CaYck2 perturbs carbon metabolism, leading to a transcriptional response that resembles a transcriptional response to glucose starvation with coinciding intracellular accumulation of glucose and depletion of TCA cycle metabolites. This shift in the metabolome is likely mediated by derepression of glucose-repressed genes in the Mig1/2-mediated glucose sensing pathway and by downregulation of glycolytic genes, possibly through the Rgt1-mediated SRR pathway. In addition, genes involved in beta-oxidation, glyoxylate cycle, oxidative stress response, and arginine biosynthesis were upregulated in the yck2Δ strain, which is highly reminiscent of C. albicans engulfment by macrophages. This coincides with an increase in arginine degradation intermediates in the yck2Δ strain, suggesting arginine catabolism as a potential mechanism of CaYck2-mediated filamentation as seen during C. albicans escape from macrophages. Transcriptome analysis also shows differential expression of hyphal transcriptional regulators Nrg1 and Ume6. This suggests dysregulation of hyphal initiation and elongation in the yck2Δ strain which may lead to the constitutive pseudohyphal phenotype of this strain. Metabolome analysis also detected a high abundance of methyl citrate cycle intermediates in the yck2Δ strain, suggesting the importance of CaYck2 in this pathway. Taken together, we discovered that CaYck2 is an integral piece of carbon metabolism and morphogenesis of C. albicans.